Linguocultural Perspectives on the Human Concept in the Context of National and Global Cultural Values (Wire Insights: Journal of Innovation Insights, 2026)
This research explores the linguocultural interpretation of the concept HUMAN within the framework of national and global value systems. The study is conducted on the basis of English and Uzbek linguistic data and focuses on identifying the semantic, cognitive, and cultural characteristics of the concept. Particular emphasis is placed on the internal structure of the concept, including its core and peripheral components, as well as on distinguishing universal and culturally specific elements. The analysis indicates that the conceptual core reflects common anthropological constants shared across cultures, while the peripheral layer contains meanings shaped by national and cultural traditions. The findings reveal the dynamic transformation of the HUMAN concept in the context of globalization and contribute to the advancement of linguocultural and cognitive linguistic research in a comparative perspective.